EKSPLORASI DAMPAK PROGRAM PPG TERHADAP PROFESIONALISME GURU LINTAS DISIPLIN DI SEKOLAH DASAR: STUDI KUALITATIF DI SDN 004 SALO - Rizki Ananda; Maisuri, Amanda; Tri Awlia Br Saragih; Ramadania Istigfarin; Indah Permata Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the impact of the Teacher Professional Education Program (PPG) on the professional development of elementary school teachers with PGSD and non-PGSD educational backgrounds at SDN 004 Salo. Using a descriptive qualitative approach, data were collected through semi-structured interviews with two teachers from different academic paths and triangulated using school documents. The findings reveal that PPG significantly enhances pedagogical competence, classroom management, holistic assessment practices, and technology-based learning creativity. Non-PGSD teachers faced greater challenges in mastering thematic instructional syntax and understanding the unique characteristics of elementary students but were supported through school-based learning communities and structural support. The study concludes that the effectiveness of PPG is strongly influenced by teachers' initial academic backgrounds and institutional environments. The implication highlights the need for adaptive PPG policies and strengthened continuous professional development systems at the primary education level.